An Analytical Study on Affect of Pandemic Covid-19 on Mutual Fund Industry in Indian - Velivala, Sreenivas; Abraham, A Francis; Kotishwar, A (The journal of contemporary issues in business and government, 2023)
The benevolent success of mutual fund sector in India has witnessed the impeccable development in the under management of asset to great extent in the recent past. The steps taken up by the regulatory body were promising and friendly for the investors and had given healthy competition globally. The occurrence of corona virus disease has impacted the mutual fund sector to great extent. The occurrence of the disease was completely unpredicted and had not given any scope of being proactive to the disease. Whenever such natural calamities have occurred, they aggressively showed their presence and arrival to the investment world and other business operations. Purpose – the purpose of this study is to find out the Impact of corona virus disease on Indian mutual fund sector, especially while the entire world is facing severe financial crisis and funds allocation plays a significant role. Data / Design/ Methodology/ Approach – the data collected and treated properly by using statistical tools and SPSS Findings – in the findings it was found that most of the investors believed that adopting a hybrid change was the right option as the sector shown some drift and flexibility also to takeover the condition. Originality / Value – the research was conducted keeping the research ethics in mind, and seen that data collected is genuine and authentic.